2023
DOI: 10.1038/s41598-023-33505-4
|View full text |Cite
|
Sign up to set email alerts
|

The association of dietary and lifestyle indices for insulin resistance with the risk of cardiometabolic diseases among Iranian adults

Abstract: The current study aimed to examine the possible association of the dietary index for insulin resistance (DIR) and the lifestyle index for insulin resistance (LIR), determined by dietary components, body mass index, and physical activity, with the risk of cardiometabolic diseases, including insulin resistance (IR), hypertension (HTN), diabetes, and metabolic syndrome (MetS). This prospective cohort study was performed on 2717 individuals aged ≥ 19 years in the framework of the Tehran Lipid-Glucose Study. Data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Our study shows that a higher ELIR is significantly associated with the increased risk of hyperuricemia. The results of our study are in line with the findings of previous studies that reported the direct association of ELIR score with increasing the risk of various chronic diseases such as cardiometabolic diseases [ 17 ], coronary heart disease outcomes [ 28 ], and diabetes [ 29 ]. At the same time, we have not seen this association in the EDIR score.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study shows that a higher ELIR is significantly associated with the increased risk of hyperuricemia. The results of our study are in line with the findings of previous studies that reported the direct association of ELIR score with increasing the risk of various chronic diseases such as cardiometabolic diseases [ 17 ], coronary heart disease outcomes [ 28 ], and diabetes [ 29 ]. At the same time, we have not seen this association in the EDIR score.…”
Section: Discussionsupporting
confidence: 92%
“…Each item (BMI, physical activity (MET.h/wk. ), and dietary components) was multiplied with their weights, and then values for all items of EDIR and ELIR were summed to attain their final score [ 17 ]. The higher EDIR and ELIR index scores indicate the potential role of diet and lifestyle items in elevating the risk of insulin resistance [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although the association between ELIR score and the risk of NAFLD has not been investigated previously, several studies have assessed the possible association of this lifestyle insulinemic index with chronic disorders risk, such as IR (Mokhtari et al, 2021), chronic kidney disease (Farhadnejad et al, 2023), cardiometabolic diseases (Teymoori et al, 2023), breast cancer (Mokhtari et al, 2023), CVDs, chronic heart disease outcomes (Teymoori et al, 2022) and type 2 diabetes (Farhadnejad et al, 2021) that indicating interesting findings. Our findings are in agreement with the results of a cohort study in Iran, which has reported that a lifestyle with a higher ELIR score was associated with an increased type 2 diabetes risk (Farhadnejad et al, 2021).…”
Section: Dietary and Lifestyle Indicesmentioning
confidence: 99%
“…Another study showed that a lifestyle with higher insulinemic potential can be linked to an increased risk of IR and hyperinsulinemia (Mokhtari et al, 2021). Two cohort studies conducted among Iranian adults revealed that high insulinemic potential of lifestyle, determined by higher score of ELIR, may be associated with increased risk of CVD events and cardiometabolic diseases, such as MetS, type 2 diabetes and hypertension (Teymoori et al, 2023;Teymoori et al, 2022). Also, it has previously been suggested that lifestyle with a high ELIR score can be associated with an increase in the risk of CKD incidents (Farhadnejad et al, 2023).…”
Section: Dietary and Lifestyle Indicesmentioning
confidence: 99%
“… 15 In contrast, Teymoori et al.’s study reported a positive relationship between EDIR and the risk of MetS. 16 As the impact of dietary patterns on metabolic syndrome may vary across different populations and demographic groups, a comprehensive understanding of the association between EDIH, EDIR, and metabolic syndrome is essential for developing personalized dietary interventions tailored to specific populations. Therefore, the current cross‐sectional study aimed to assess the relationship between EDIH and EDIR with the risk of metabolic syndrome and its components in an Iranian population.…”
Section: Introductionmentioning
confidence: 98%